Urban-Rural Disparities in Multidimensional Poverty: A Cross-Country Econometric Analysis Using MPI Data - Shilpa Sree R; Singh, Anurag Vikram (Journal of Regional Economics and Development, 2026)
Urban–rural disparities in poverty remain a persistent challenge despite significant global progress in poverty reduction. Conventional income based measures often fail to capture the multiple and overlapping deprivations experienced by households, particularly in rural areas. This study aims to examine the magnitude, structure, and determinants of urban–rural disparities in multidimensional poverty using the global Multidimensional Poverty Index (MPI). Employing a cross-country econometric research design, the study integrates national-level and subnational-level MPI data covering more than 100 countries and approximately 1,000 regions. The empirical analysis combines descriptive techniques, ordinary least squares (OLS) regression, and linear mixed-effects modeling to capture both between-country and within-country variations in multidimensional poverty. The results reveal substantial and unevenly distributed urban–rural MPI gaps across countries, with particularly pronounced disparities observed in several Sub-Saharan African economies. Regression findings indicate that differences in poverty incidence, measured through the headcount ratio gap, are the dominant driver of the urban–rural MPI gap, while differences in deprivation intensity play a statistically significant but secondary role. The multilevel analysis further demonstrates a strong and near-proportional transmission of national-level multidimensional poverty to regional outcomes, underscoring the importance of national development trajectories in shaping subnational poverty patterns. The study concludes that urban–rural disparities in multidimensional poverty are primarily driven by unequal access to basic services and opportunities rather than solely by the depth of deprivation. These findings highlight the need for multidimensional and multi-level policy interventions that simultaneously reduce poverty incidence and address overlapping deprivations, particularly in rural areas, to achieve inclusive and balanced development